Design and Implementation of Secure and Scalable Distributed Computing Systems for Modern Applications - Partha Sarothi; Zulfiqur Rahman; Amrita Khan; Amit Kumar; Kamal Khan (The Eastasouth Journal of Information System and Computer Science, 2024)
The rapid growth of modern applications, including cloud computing, big data analytics, and Internet of Things (IoT), has significantly increased the demand for secure and scalable distributed computing systems. Traditional centralized architecture is no longer sufficient to handle large-scale data processing and dynamic workloads, leading to the adoption of distributed computing paradigms. This study presents the design and implementation of a secure and scalable distributed computing framework, supported by performance evaluation through analytical figures illustrating system scalability, resource utilization, latency, and security effectiveness. The analysis demonstrates that distributed architectures significantly improve system scalability by enabling horizontal scaling and efficient workload distribution across multiple nodes. The figures highlight that as the number of nodes increases; system throughput improves while latency is reduced through optimized communication and load balancing mechanisms. Additionally, the implementation of advanced security protocols, including encryption, authentication, and access control, enhances system resilience against cyber threats. The results further indicate that the integration of containerization and orchestration technologies, such as Kubernetes, improves resource utilization and system reliability. Security evaluation metrics show a reduction in vulnerability exposure and improved threat detection capabilities in distributed environments. However, the figures also reveal challenges related to network latency and resource management, particularly in highly dynamic environments.